(untitled) (Proceedings of International Educators Conference, 2023)
Russian after the establishment of Turkestan Governor General the migration of part of the population to the territory of the colony (second stage) began. According to the instructions of the St. Petersburg authorities and the colonial administration, new, including The fact that tax and other benefits, which were given to those who moved arbitrarily, and those who first came and settled in the vicinity of Russian fortresses and fortifications, were preserved, encouraged such migration. Economic destruction, frequent crop failures, and the continuation of landlord oppression led them to Turkestan. They were mainly Russians, Ukrainians, and partly Germans who had immigrated from Astrakhan, Voronezh, Samara, Kharkov, and Orenburg regions. Although most of these migrations took place on the initiative of the peasants, the colonial authorities helped them in every way to resettle them, provide them with land and restore their farms. This article discusses the source studies of the resettlement policy implemented during the Turkestan Governor General’s term.